Policy and assessment. Issue 3 (3rd July 2019) - Colwell, Richard
Abstract: As the title suggests, the author provides a description of an international effort to develop an understanding of the present depth and priority of arts policies. As arts policy is not limited to education but formulated at all levels of community, including unions, individuals, philanthropic organizations, and government agencies, policy often becomes political. Arts policy is complex. For some arts policy is little more than participation, hence the conclusion of the Organisation for Economic Co-operation and Development study sponsored by France and Germany that, despite the absence of positive results from the studies objectives, the authors declared value "in the experience." The education community tends to focus on public–private school advocacy, rather than arts policy. Surprisingly, there is an absence of arts policy in teacher education. The research of Elpus indicates no drop in school participation in the arts and results from the Bill & Melinda Gates Foundation study on teacher education with little public concern for arts assessment. The German concept of Buildung is sufficiently broad to establish a foundation for a rigorous, culturally based art policy, with democratic moral and aesthetic principles applicable for individual communities. Policy makers value assessment data, often adopting data from objectives rather than from the goals that are foundational for policy. With any data, validity and how the data are interpreted is essential for public trust.